Thrombus or tumor?: A case report of a rare sarcoma entity: intimal sarcoma of the pulmonary arteries - Dörr, Anne; Flörcken, A; Bullinger, L.; Capper, D.; Deimling, Andreas von; Kaul, D.; Märdian, S.; Starck, C.; Horst, D.; Dragomir, M.P.; Schäfer, F.M.; Jarosch, A. (Molecular biology reports, 2024)
Tumor embolism is a very rare primary manifestation of cancers and the diagnosis is challenging, especially if located in the pulmonary arteries, where it can mimic nonmalignant pulmonary embolism. Intimal sarcoma is one of the least commonly reported primary tumors of vessels with only a few cases reported worldwide. A typical location of this malignancy is the pulmonary artery. Herein, we present a case report of an intimal sarcoma with primary manifestation in the pulmonary arteries.
Online veröffentlicht: 24. April 2024
Gesehen am 27.09.2024